Antioxidant Activity of Virgin Coconut Oil Emulsion Drink with The Addition of Cinnamon (Cinnamomum burmanii) - G.S. Suhartati Djarkasi; Maria Fransisca Sumual; Lana E. Lalujan; Ambar Kurnia; Jeanet Rotulung (Sam Ratulangi University, 2024)
ABSTRACT The aims of this study were to analyse the antioxidant activity and to determine the maximum concentration of cinnamon extract that can improve sensory attributes of VCO emulsion drink. The research method used is a completely randomized design (CRD) with five concentrations of cinnamon extract, i.e., 0% (P1), 2% (P1), 4% (P2), 6% (P3), and 8% (P3). Each treatment was triplicated. The results showed that all treatments exhibited stable emulsion with 0% creaming index. VCO emulsion drink with cinnamon extract contained total phenol ranged from 19.88 mg GEA/100 g to 28.58 mg GEA/100 g, with increasing antioxidant activity, expressed as percentage of inhibition, where P1: 80.35%; P1: 85.59%; P2: 86.38%, P3: 87.43%, and P4: 88.54%, respectively. It was concluded that cinnamon extract could increase the antioxidant activity of VCO emulsion drinks. Increasing percentage of cinnamon extract can increase the total phenol content, hence increase the inhibitory power on the formation of peroxide compounds. The addition of 6% cinnamon is the maximum limit that can improve the panellists’ liking for the overall sensory attributes of the VCO emulsion drink. Keywords: Antioxidant activity; cinnamon; VCO emulsion